2020
DOI: 10.1002/chem.202000840
|View full text |Cite
|
Sign up to set email alerts
|

Reversible N‐Heterocyclic Carbene‐Induced α‐H Abstraction in Tungsten(VI) Imido Dialkyl Dialkoxide Complexes

Abstract: The first reversible N‐ heterocyclic carbene (NHC) induced α‐H abstraction in tungsten(VI) imido‐dialkyl dialkoxide complexes is reported. Treatment of W( N Ar)(CH 2 Ph) 2 (O t Bu) 2 (Ar=2,6‐dichlorophenyl, 2,6‐dimethylphenyl, 2,6‐diisopropylphenyl) with different NHCs leads to the formation of complexes of the type W( N Ar)(CHPh)(NHC)(CH 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…20 To prove this assumption, we reacted W(N-2,6-Cl 2 − C 6 H 3 )(OtBu) 2 Cl 2 (THF) with 3.0 equiv of the sterically less demanding benzylmagnesium chloride. Although we recently showed that also dibenzyl complexes of the type W(NAr)-(CH 2 Ph) 2 (OtBu) 2 (Ar = 2,6-Me 2 -C 6 H 3 , 2,6-i Pr 2 -C 6 H 3 , 2,6-Cl 2 -C 6 H 3, ) can be synthesized, 31 in fact in this case, the corresponding tribenzyl complex W(N-2,6-Cl 2 -C 6 H 3 )-(CH 2 Ph) 3 (OtBu) (see the Supporting Information for its single crystal X-ray structure) was isolated in 42% yield. Here, no substitution of the second alkoxide occurred, which can again be attributed to the lower steric bulk of the benzyl groups compared to the neophyl groups in, e.g., W-4b.…”
mentioning
confidence: 99%
“…20 To prove this assumption, we reacted W(N-2,6-Cl 2 − C 6 H 3 )(OtBu) 2 Cl 2 (THF) with 3.0 equiv of the sterically less demanding benzylmagnesium chloride. Although we recently showed that also dibenzyl complexes of the type W(NAr)-(CH 2 Ph) 2 (OtBu) 2 (Ar = 2,6-Me 2 -C 6 H 3 , 2,6-i Pr 2 -C 6 H 3 , 2,6-Cl 2 -C 6 H 3, ) can be synthesized, 31 in fact in this case, the corresponding tribenzyl complex W(N-2,6-Cl 2 -C 6 H 3 )-(CH 2 Ph) 3 (OtBu) (see the Supporting Information for its single crystal X-ray structure) was isolated in 42% yield. Here, no substitution of the second alkoxide occurred, which can again be attributed to the lower steric bulk of the benzyl groups compared to the neophyl groups in, e.g., W-4b.…”
mentioning
confidence: 99%
“…Our group has a long-standing track record in the synthesis of group 6 olefin metathesis catalysts bearing an NHC ligand. In previous studies, we found that five-coordinate NHC complexes usually possess high activity and functional group tolerance; the activation of those complexes occurs via a cationic species. , Indeed, later we succeeded in isolating cationic group 6 complexes that were outstandingly active (TON of up to 1.2 million for silica-supported cationic catalysts). ,, However, we noticed that certain representatives of the five-coordinate, neutral complexes were only active at elevated temperatures and some of those complexes were even completely inactive, which is especially true for tungsten-based catalysts. , …”
Section: Results and Discussionmentioning
confidence: 96%
“…In many cases, cis-isotactic (cis-it), trans-isotactic (trans-it), cis-syndiotactic (cisst), or trans-syndiotactic (trans-st) structures are formed virtually selectively. [7,8] More recently, the new class of cationic DOI: 10.1002/macp.202200350 molybdenum and tungsten alkylidene NHC catalysts bearing imido, oxo and sulfido ligands, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] respectively, has been developed. Compared to Schrock-type catalysts, this class of catalysts is characterized by a generally increased tolerance toward oxygen, moisture and functional groups [14,15,29] as well as by higher activities and productivities with turnover numbers exceeding 1.2 million when supported on silica.…”
Section: Introductionmentioning
confidence: 99%